Confocal laser scanning microscopy investigation of bond interfaces involved in fiber glass post cementation - Fagundes, Ticiane Cestari [UNESP]; Somensi, Daniele Salazar; Santos, Paulo Henrique dos [UNESP]; Navarro, Maria Fidela de Lima (Editora Cubo, 2014)
Objective: This confocal microscopy study evaluated the cement/dentin and cement/post interfaces along theroot canalwallswhenfiberglasspostswerebonded to dentin using different types of cements. Material & Methods: Thirty endodontically treated premolars were divided into 3 groups according to the adhesive materials used in the bonding procedure: Prime & Bond 2.1/Self Cure + Enforce, RelyX Unicem and RelyX Luting. Rhodamine B dye was incorporated in the luting materials for the cementation of the fiber glass posts (Exacto, Angelus) to dentin. Three transversal slices (apical, middle and coronal) were examined under confocal laser scanning microscopy. Statistical analysis was performed using the Kappa, Kruskal-Wallis and Dunnet tests, in a significance level of 5%. Results: The Prime & Bond 2.1/Self Cure + Enforce presented a uniform formation of tags in the dentin but gaps in the cement/dentin interface. The RelyX Unicem and RelyX Luting presented an adhesive interface with a fewer amount of gaps, but showed shorter tag formation than the Enforce system. All cements presented the same pattern of bubbles inside the cements. The RelyX Luting presented a greater amount of cracks inside the cement in comparison with the other cements in the coronal third, while no difference was observed between RelyX Unicem and Enforce. The RelyX Luting showed the lowest quantity of cement penetration into the post. Conclusion: In general, the quality of bonding interfaces of fiber posts luted to root canals was affected by both location and type of cement.

Objetivo: O objetivo deste trabalho foi avaliar as interfaces cimento/dentina e cimento/pino quando diferentes agentes cimentantes foram utilizados na cimentação de pinos de fibra de vidro. Material e Métodos: Trinta pré-molares humanos foram tratados endodonticamente e divididos em 3 grupos de acordo com o procedimento adesivo: Prime & Bond 2.1/Self Cure + Enforce, RelyX Unicem e RelyX Luting. Corante fluorescente Rodamina B foi incorporado aos agentes cimentantes para a cimentação dos pinos de fibra (Exacto, Angelus). Os dentes foram seccionados em três terços (apical, médio e coronário) e examinados ao microscópio confocal. Os dados foram submetidos aos testes Kappa, Kruskal-Wallis e Dunnet, a um nível de significância de 5%. Resultados: O grupo Prime & Bond 2.1 / Self Cure + Enforce apresentou uma formação uniforme de tags na dentina, porém fendas na interface cimento/dentina. Os cimentos RelyX Unicem e RelyX Luting apresentaram uma interface adesiva com pequena quantidade de fendas, mas mostrou pequena formação de tags se comparados ao sistema Enforce. Todos os cimentos apresentaram o mesmo padrão de bolhas em seu interior. O cimento RelyX Luting apresentou grande quantidade de trincas em seu interior se comparado com os outros cimentos no terço coronário, enquanto nenhuma diferença foi observada entre os cimentos RelyX Unicem e Enforce. O cimento RelyX Luting a menor quantidade de penetração de cimento dentro do pino. Conclusão: Em geral, a qualidade das interfaces adesivas dos cimentos foi afetada pela localização e tipo de cimento.
Avaliação de dentes restaurados com pinos de fibra de vidro e agentes cimentantes, empregando-se microscopia confocal
Keywords: Canals; Bonding techniques; Dentin; Cements; Canal; Técnicas adesivas; Dentina; Cimentos